Delivery Work and the Experience of Social Isolation - Seetharaman, Bhavani; Pal, Joyojeet; Hui, Julie (CSCW, 2021)
The isolating nature of platform-based work, particularly gig work involving deliveries, has created unintended consequences over how workers engage with peers, friends, family, and society in general. We performed a qualitative study involving interviews with 21 delivery workers in Bangalore, India to understand how workers experienced and responded to social isolation perpetuated by the nature and daily function of their work. We found that the stigma and individual nature of app-based delivery work restricts access to inter-relational and instrumental support. As a response, workers organized peer networks for both companionship and emergency assistance. We analyze how the cultural context of India heightens these experiences, and offer ideas for mitigating the risks of isolation as a result of gig work.